Analysis Of Teaching Skill Of Prospective Physical Education Teachers Through Video Tape Feedback (VTFB) - Rahmadarni, Nadia Desturia; Usra, Meirizal; Bayu, Wahyu Indra; Iyakrus, Iyakrus; Yusfi, Herri (Universitas Negeri Semarang, 2025)
Introduction: The success of Physical Education (PE) learning greatly depends on the quality of the teacher’s instruction. Many pre-service PE teachers still demonstrate low teaching skills, particularly in lesson planning, classroom management, instructional delivery, and reflective ability. These challenges limit the effectiveness of the learning process and contribute to low performance in teaching assessments and field teaching practice. Objectives: This study aims to analyze the teaching skills of prospective Physical Education teachers through the application of the Video Tape Feedback (VTFB) method as a reflective tool to enhance teaching performance. Method: A cross-sectional research design was employed with 58 pre-service teachers from FKIP Universitas Sriwijaya, cohort2024. Data were collected through observations, video recordings, and document analysis using an instrument consisting of 12 core teaching skill components.Result: The study shows that reviewing their own teaching through VTFB helps pre-service teachers notice things they often miss when they are in the classroom.By watching the recordings, they tend to see their weak spots more clearly and can think back on their decisions in a more honest and practical way. Many of themalso become more aware of how they explain lessons, how they handle the class, and how they respond to students during activities. Supervisors and spectatorsmay overlook what happens during education in video reviews. VTFB improves PE teacher candidates overall. Conclusion: The findings suggest that teachereducation programs should employ this method to promote continuous learning and consistent performance evaluation.